PENGARUH LINGKUNGAN KERJA DAN MOTIVASI INTRINSIK TERHADAP KREATIVITAS GURU SMA NEGERI KOTA BANDAR LAMPUNG - Asef Riyadi (Jurnal Manajemen Pendidikan, 2014)
The objectives of this research was to investigate and to understand the effect of work environment and intrinsic motivation on creativity. It was a quantitative research which was conducted in three state senior high schools in Bandar Lampung City located in Lampung Province. The research used a survey method with path analysis applied in testing hyphotesis. The respondent sample are 177 teachers who are selected in a simple random way. The result of this research are: (1) There is a direct positive effect of work environment on creativity. (2) There is a direct positive effect of intrinsic motivation on creativity. (3) There is a direct positive effect of work environment on intrinsic motivation.